HIV vulnerabilities of sex-trafficked Indian women and girls. - Gupta, Jhumka; Raj, Anita; Decker, Michele R; Reed, Elizabeth; Silverman, Jay G (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2009)
To qualitatively explore potential mechanisms that may confer heightened risk for HIV infection among survivors of sex trafficking in India.
Keywords: Adaptation, Psychological; Adolescent; Adult; Condoms; Female; Health Services Accessibility; HIV Infections; Humans; India; Personal Autonomy; Prostitution; Rape; Retrospective Studies; Risk; Sex Offenses; Substance-Related Disorders; Survivors; Young Adult